Neural Network Modelling of Organizational Capabilities in Achieving Sustainable Competitive of Start-Up - Khababa, Nourredine; Mekimah, Sabri; Zighed, Rahma; Bengana, Ismail; Alrawad, Mahmaod; imane, Benaouali (Journal of Ecohumanism, 2024)
Aim/Purpose-This study aims at identifying the role of organizational capabilities in achieving sustainable competitive advantage of start-up. Design/methodology/approach –The analytical descriptive approach was adopted, by introducing the study variables theoretically, represented in both the organizational capacity variable and the sustainable competitive advantage. As for the applied part, in order to collect data, a form was designed and distributed to a random sample of 255 Start-ups in Algeria. Moreover, so as to address and test the hypotheses of the study, the neural network modelling method was used, based on the Matlab program. Findings –The study concluded that the dimensions of organizational capabilities contribute very weakly to achieving sustainable competitive advantage of start-ups, especially after organizational flexibility and organizational creativity, as they contribute together by 52.5%, which is an average percentage. Research implications/limitations – The start-ups should pay more attention to applying the dimensions of organizational capabilities which helps to achieve a sustainable competitive advantage. Originality/value/contribution –The importance of the study lies in the fact that it deals with a recent topic represented in organizational capabilities and sustainable competitive advantage in the field of scientific research and the scarcity of studies and research related to it. Furthermore, it is one of the first studies that apply organizational capabilities in Algerians start-ups. Thus, we hope that it would be a scientific reference that can be used in corporate development.